Autism spectrum disorders and coexisting disorders in a nationwide Swedish twin study. (3rd October 2014) - Lundström, Sebastian; Reichenberg, Abraham; Melke, Jonas; Råstam, Maria; Kerekes, Nóra; Lichtenstein, Paul; Gillberg, Christopher; Anckarsäter, Henrik
<x xml:space="preserve">Abstract</x> Background Evidence from twin and molecular genetic studies is accumulating that Autism Spectrum Disorder (ASD) shares substantial etiological factors with other disorders. This is mirrored in clinical practice where ASD without coexisting disorders is rare. The present study aims to examine the range of coexisting disorders in ASD in a genetically informative cohort. Methods Parents of all Swedish 9‐year‐old twins born between 1992 and 2001 (n = 19, 130) underwent a telephone interview designed to screen for child psychiatric disorders, including ASD. To ensure full coverage of child psychiatric disorders, data were also retrieved from population‐based health registers. We investigated the coexistence of eight psychiatric disorders known to coexist with ASDs in probands and their co‐twins. Results Half of the individuals with ASDs (50.3%) had four or more coexisting disorders and only 4% did not have any concomitant disorder. The 'healthy co‐twin' in ASD discordant monozygotic twin pairs was very often (79% of boys and 50% of girls) affected by at least one non‐ASD disorder. The corresponding figures for ASD discordant dizygotic twin pairs were significantly lower (46% of males and 30% of females). Conclusions Detailed phenotypic descriptions including symptoms of problems associated with a wide range of child psychiatric disorders may aid in unraveling the genetic architecture of ASD and should guide the development of intervention strategies addressing each problem type specifically.